Socio-Cultural Traditions, Ecological Features and Indigenous Practices in Spiti Valley of Trans-Himalayan Region: Understanding Rationale and Implications for Natural Resource Conservation and Agricultural Development - Sharma, H R; Chouhan, S K (Annals of Arid Zone, 2016)
The present study, carried out in trans-Himalayan region of Himachal Pradesh, shows that the most important ecological changes in people’s perceptions, inter alia, are decrease in area under forests, wastelands, fallow and common lands. The study also shows that while there is no significant change in food habits, the dress culture has witnessed a most conspicuous change. Further, a less number of festivals and fairs are now celebrated as compared to a decade ago. Another most notable positive social change has been a significant increase in the enrolment of boys and girls in schools and positive attitude of people towards small family. However, notwithstanding spread of literacy and increasing awareness among local population, a number of superstitions are still practiced. Among indigenos practices, rules and regulations for maintaining and sharing water resources, sharing labor, crop rotation and the practice of primogeniture have positive implications towards conservation of natural resources and agricultural development. Key words: Spiti Valley, land use, ecology, education, traditional practices.